Coverage and adequacy of minimum income schemes in the European Union - Francesco Figari; Tina Haux; Manos Matsaganis; Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2010)
The purpose of this paper is to explore and compare the effectiveness of Minimum Income (MI) schemes in protecting people of working age from poverty in the European Union. Using the EU-wide microsimulation model EUROMOD, we investigate (a) coverage and (b) adequacy of MI schemes in 18 countries. In contrast to previous comparative studies of MI benefits, relying on comparisons of the effects on stylised families, we are able to capture the full range of individual and household circumstances and to quantify the effects on people entitled to MI schemes using a comparable approach across countries.
Keywords: C81; H53; I38; 330; Minimum Income; European Union; Microsimulation; Adequacy; Coverage; Armutspolitik; Arbeitskräfte; Mindestlohn; EU-Staaten